Advocating for The Sustainability of Semai Indigenous Music Through The Collaborative Creation of New Traditional Music: A Participatory Action Research (PAR) Methodology - Chan, Clare Suet Ching; Saidon, Zaharul Lailiddin (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2021)
This article provides a critical reflection on the participatory approach methodology and the collaborative creation approach used in an advocacy project to sustain the musical heritage of the indigenous Semai community in Malaysia. These approaches were examined through the medium of an advocacy project that aimed to stimulate the interest of Semai youth in traditional music through relevance, engagement, and connection with their current musical interest and skills. The intention of the project was to also co-create new traditional music with the Semai youth through live musical interaction, improvisation and jam sessions with the research team. This article explored the research teamâ€™s use of the â€œParticipatory Action Researchâ€ (PAR) method, which involved planning, action, observation, reflection, and revision during the initial stages of our advocacy project. Our findings suggest a narrative style in discussing advocacy processes because they occur in a lateral than the linear or cyclical format used in current action research models. Findings also reveal that any attempts to advocate change in the community would firstly require an established relationship of trust, respect, and belief in the research team. The research team would have to have had prior involvement, commitment, and dedication to the community before members of the team could influence change among the community. A self-review of the research teamâ€™s effort to co-create new traditional music with Semai youth led to the conclusion that co-creation between musicians of different musical training would require a â€œnewâ€ compositional method that negotiates Western musical composition techniques with the oral tradition of creating music.